Themes of cultural-historical heritage and animation methods in art education present in teachers questionnaire statements - Zuzana Pechová (Czech Pedagogical Society, 2012)
The study discusses the animation of cultural historical heritage from educational perspective and its use in the school environment. Theoretical framework presents a contemporary perception of those two phenomena and is followed by interpretation of results of a questionnaire survey. The survey was conducted in Czech lower secondary schools in the Liberec region in 2011. The aim of the research was to investigate how the topics are present in art education and how they are perceived by teachers of art education. The research sample consisted of 81 teachers and provided answers to 9 questions. The analysis, classification and categorising of the results indicates a focus on artistic themes as preferred field of cultural historical heritage for teaching with the objectives of overall development of students personality. Due to the vague idea about the animation method, the cultural historical heritage theme presented by animation is almost not used.